COMPARISON OF THE CONTENTS OF TECHNICALLY ORIENTED SUBJECTS IN PRIMARY SCHOOLS IN THE CZECH REPUBLIC AND SLOVAK REPUBLIC - LUKACOVA, Danka (Trends in education, 2012)
Department of Technology and Information Technology at the Faculty of Education of Constantine the Philosopher University in Nitra works with the Department of Technical Education and Information Technology at the Faculty of Education of Palacky University in Olomouc in the establishment of common support materials to teach technically oriented subjects in primary schools. The author of the article analyzes the content of these objects, comparing them and looking for common points.
Keywords: technically oriented subjects; the public education program; general education program.